The spectrum of acute and subacute myelopathy - Silber, Michael H (Division of Urology, 2018)
Acute and subacute diseases causing intrinsic spinal cord damage are confusing and poorly defined clinically and pathologically. of this study is: The purpose 1. To analyse the spectrum of conditions responsible for acute and subacute myelopathy in South Africa. 2. To categorise the clinical presentations and prognosis of the illnesses and to correlate these with aetiology. 3. To assess the validity of diagnostic criteria for acute and subacute myelopathy in general and for the different aetiological groups. 4. To review the literature and to correlate previous studies with the present one. Thirty-four patients fulfilling strict criteria nave been identified over a seven-and-a-half-year period using the Groote Schuur Hospital computer retrieval system. Although the study was essentially retrospective, 11 of these patients were seen personally during their acute illnesses. All these patients have suffered from illnesses causing spinal cord dysfunction in the absence of trauma, physical agents or any extrinsic pressure such as might be caused by tumours or spondylosis. Maximum disability was reached in less than 8 weeks. In 17 patients no cause was identified. The clinical features, laboratory findings and courses have been analysed. Among the results, a high percentage of patients with Brown-Sequard Syndromes were found with possible significance for the pathogenesis of the illness. Seven patients with meningovascular syphilis were analysed as well as 2 additional patients with spinal cord syphilis not fulfilling the strict criteria of the study. Although well known before the penicillin era, this entity is not well described in modern neurological literature. Four patients had myelopathy associated with pulmonary tuberculosis in the absence of tuberculous meningitis or spinal disease. Three of these 4 patients also developed optic neuropathy. The association of these conditions has previously been described in only a very few patients. Two patients had Epstein-Barr virus infections and 1 had an infection with Mycoplasma pneumoniae. Two had systemic lupus erythematosus and 1 had an acute cord infarct following an aortic aneurysm repair. The literature is reviewed and the findings of this study correlated with previous ones. Conclusions regarding terminology, criteria for diagnosis, investigations, course and prognosis are discussed.